PEMBINAAN KELUARGA MUALAF UPAYA MEMBENTUK PRIBADI MUSLIM - Mahmud Mahmud; Miftahul Fikri; Hasbiyallah Hasbiyallah; Anita Nuraeni (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
This article was conducted to see how far the religious formation of the converts was obtained. Because as a muslim who is new to Islam, certainly requires a religious formation to make it easier for him to understand the teachings about Islam. It aims to be able to describe how religious formation is carried out by family converts and how the results o religious formation convert to Islam, which is in accordance with Muslims in general. So that this research can be a role model for the community in carrying out religious guidance on converts. This research method uses a qualitative approach with the method of description analysis to find out more about the implementation of religious coaching for several families of convert families. The results of this study show how the process of fostering Islamic religious education carried out by several convert families in several ways and methods to increase the firmness of their faith in Islam. So as to make their faith strong and make a muslim person intact and to avoid their return to their old beliefs.